Monitoring of diclofenac with biomimetic sensor in batch and FIA systems - Wong, Ademar [UNESP]; Marestoni, Luiz D. [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP] (Sociedade Brasileira de Química, 2014)
The present work aims the development of a biomimetic sensor for the detection of sodium diclofenac from a glassy carbon electrode modified with copper(II) 1,4,8,11,15,18,22,25-octabutoxy-29H,31H-phthalocyanine complex and functionalized multi-walled carbon nanotubes (MWCNT-COOH). The proposed sensor was evaluated in batch system using 0.1 mol L-1 phosphate buffer solution at pH 7.5 as electrolyte support. A linear response was obtained in the range of 4.0 × 10-5 and 6.7 × 10-4 mol L-1, with the sensitivity of 6.1 × 10(5) (± 1.5 × 10(4)) µA L mol-1 and detection limit of 1.3 × 10-5 mol L-1 using square wave voltammetry. The selectivity was studied by the sensor response in the presence of other drugs. The sensor was applied to pharmaceutical formulations and also to biological serum samples by recovery studies. When coupled to a flow injection system (FIA), the best results were obtained by applying the potential of 0.5 V vs. Ag|AgCl|KCl sat, using an injected volume of the sample of 100 µL and a flow of 1.2 mL min-1. The linear response range in flow was between 5.0 × 10-5 and 5.0 × 10-3 mol L-1, with a sensitivity of 1.6 × 10(4) (± 3.0 × 10²) µA L mol-1and a relative standard deviation of 3.5%.

O presente trabalho visa o desenvolvimento de um sensor biomimético para detecção de diclofenaco de sódio usando um eletrodo de carbono vítreo modificado com complexo 1,4,8,11,15,18,22,25-octabutoxi-29H,31H-ftalocianina de cobre(II) e nanotubos de carbono de parede múltipla funcionalizados (MWCNT-COOH). O sensor proposto foi avaliado em sistema em batelada usando tampão fosfato 0,1 mol L-1 (pH 7,5) como eletrólito de suporte. Uma resposta linear foi obtida na faixa entre 4,0 × 10-5 e 6,7 × 10-4 mol L-1, com uma sensibilidade de 6,1 × 10(5) (± 1,5 × 10(4)) µA L mol-1 e limite de detecção de 1,3 × 10-5 mol L-1 usando voltametria de onda quadrada. A seletividade foi estudada através da resposta do sensor na presença de outros fármacos. O sensor foi aplicado em formulações farmacêuticas e também em amostras de soro biológico através de estudos de recuperação. Quando acoplado a um sistema por injeção em fluxo (FIA), os melhores resultados foram obtidos aplicando o potencial de 0,5 V vs. Ag|AgCl|KCl sat, usando um volume de amostra injetado de 100 µL e uma vazão de 1,2 mL min-1. A faixa linear de resposta em fluxo foi entre 5,0 × 10-5 e 5,0 × 10-3 mol L-1, com uma sensibilidade de 1,6 × 10(4) (± 3,0 × 10²) µA L mol-1 e um desvio padrão relativo de 3.5%.
Keywords: biomimetic catalyst; copper(II) 1,4,8,11,15,18,22,25-octabutoxy-29H,31H-phthalocyanine; diclofenac; flow injection system; MWCNT-COOH; glassy carbon electrode